BD +20°1171 - LONG - PERIODIC VARIABLE STAR - Brukhanov, I. S. (Одеські астрономічні публікації, 2017)
BD +20°1171 (= NSV 16732 = TYCHO 1320 91 1 = HD 39785 = SAO 077726) is a long-periodic pulsating variable star of SRc-type with a period of 20930d , range of variations in B 8.m8 - 10.m3, and the most realiable maximum is JD 2443410.5